Development and validation of a UV/visible spectrophotometric method for simultaneous assay of paracetamol and ibuprofen - Timothée Mavanga Mabaya; Jocelyn Mankulu Kakumba; Mannix Mayangi Makola; Adelard Mbenza Puati; Didi Mana Kialengila; Jean Mavar Tayey Mbay; Jérémie Mbinze Kindenge (Orapuh Journal)
Introduction